(untitled) (Rupandehi Campus Journal, 2024)
The article entitled "Globalization and English Language Teaching: Implication and Challenges" explores about the significance of globalization, its possibilities and challenges. As it is a systematic review article some of the national and internal articles have been purposefully selected for the critical analysis and reflection of the meanings concerning the research title.The derived data are thoroughly studied and analysed through the process of coding and decoding. Finally the results and findings are summarized in the conclusion section. The researcher has presented some recommendations based on the results and findings.